MEMAHAMI PENGGUNAAN MEDIA MANIPULATIF DALAM PEMBELAJARAN MATEMATIKA SD - Nurhaswinda; Fithri Humairo Yensah; Hazirah Rahmadhani; Izzati Eniza Amanda; Nadya Alfirdaus; Rizka Aulia (STKIP Subang, 2026)
The use of manipulative media in elementary school mathematics learning plays an important role in helping students understand abstract concepts. However, many students still experience difficulties in learning mathematics due to its abstract nature, which impacts their learning outcomes. This study aims to describe the effectiveness of manipulative media in improving students’ conceptual understanding, learning outcomes, and problem-solving abilities. The research method used is a literature review by analyzing various relevant scientific journal articles published in national journals. Data were collected through documentation techniques and analyzed descriptively by identifying, classifying, and comparing findings from previous studies. The results show that manipulative media are effective in making abstract mathematical concepts more concrete and easier to understand. In addition, the use of manipulative media can increase students’ learning motivation, engagement, and active participation during the learning process. It also contributes significantly to improving students’ problem-solving skills, as they can explore and experiment directly with learning materials. Furthermore, manipulative media are particularly effective when applied to basic mathematical topics such as addition and subtraction. Therefore, the use of manipulative media is highly recommended as an innovative and effective learning strategy to enhance the quality of mathematics learning in elementary schools.